Offshoring innovation: an empirical investigation of dyadic complementarity within SMEs - Khraishi, Ahmad; Huq, Fahian; Paulraj, Antony (Elsevier, 2020)
Despite scholarly agreement that complementary capabilities are essential to successful collaborations, little is known about how small and medium-sized enterprises (SMEs) manage collaborative innovation through offshoring. Besides, the innovation management literature remains generally silent about when supplier joint actions could work in enhancing offshoring innovation (OI) performance. The purpose of this study is twofold. First, we aim to delineate why supplier's asset specificity and goal compatibility predict supplier's complimentary capabilities in OI. Second, we empirically explore the role of supplier joint actions in enhancing OI performance. Based on data collected from 200 SMEs having active OI relationships spanning four developed European countries, our results propose that supplier's complementary capabilities mediate the relationship between critical relational antecedents (supplier's asset specificity and goal compatibility) and OI performance. It should be noted, however, that despite their incentivising power, supplier joint actions can be a “double-edged sword” in SMEs’ OI relationships.